DISTRIBUSI LOGAM BERAT PADA AIR DAN SEDIMEN LAUT DI WILAYAH PESISIR KABUPATEN SUMBAWA BARAT - Helmy Akbar; Ario Damar; Mohammad Mukhlis Kamal; Kadarwan Soewardi; Singgih Afifa Putra (Journal Omni-Akuatika, 2015)
Mineral mining (i.e. gold) activities in the land and coastal boundaries of West Sumbawa district are expected to increase the content of heavy metals in the marine and coastal waters surrounding. A residual of mining processing produce heavy metals disposal. In this study, the distributions of heavy metals (i.e. Hg, Cr6+, Cu, As, Ni, Zn, Pb, and Cd) were measured in the water column and bed sediments of coastal waters of West Sumbawa. This study was conducted during dry season in July 2011. The results showed the heavy metal concentrations in water column were below the threshold level stipulated by the Minister Decree No. 51/2004, except for Cu. The heavy metal contents in bed sediment were low and varied among sampling points excepting for Cu content which was remarkably high (101,7 mg/Kg).